Teachers' ideas about children's right to participate in ECE - Correia, N.; Carvalho, H.; Durães, J.; Aguiar, C. (EECERA 29th Annual Conference, 2019)
We aim to investigate teachers' ideas about children's right to participate in early childhood education (ECE), identifying complex profiles of teachers' ideas, and exploring associations between profiles and individual/contextual variables. Research highlights the relevance of promoting children's right to participate in ECE (Sheridan & Samuelsson, 2001), as an indicator of ECE quality (Sheridan, 2007), and emphasizes ECE teachers' role, namely their ideas to its promotion (Sandberg & Eriksson, 2010). Children's right to participate refers to children's right to exert influence in all matters affecting them, freely expressing opinions and having them considered (United Nations, 1989), through shared decision-making with adults (Venninen, Leinonen, Lipponen, & Ojala, 2014). Teachers' beliefs are crucial for understanding/improving educational practices (OECD, 2009), being influenced by individual characteristics (Faour, 2003). Participants were 59 ECE teachers (26-60 years old), from 59 randomly selected ECE settings (Lisbon area). Information on teachers' education, experience, pedagogical models, and institution/group was gathered. A qualitative interview was conducted, followed by content analysis, multiple correspondence analysis and cluster analysis. Authorization obtained from National Commission for Data Protection, University Ethics Committee; teachers and parents' written consent, children's assent; all data protected with codes. Four profiles of teachers' ideas about participation were identified: 'Teachers' motivation'; 'Teachers' conditioned responsibility'; 'Children's' benefits'; 'Context dependent'. Teachers' profiles are significantly associated with years of professional experience and type of institution. Age is significantly different across profiles. We provide additional insights to a fuller understanding of teachers' positioning about this topic, useful to inform research addressing multiple levels of child participation.